Next-Generation Sequencing Infertility Panel in Turkey: First Results - Ikbal Atli E; Yalcintepe S; Atli E; Demir S; Gurkan H (Balkan Journal of Medical Genetics)
Male infertility is a complex pathophysiological disorder. At least 2000 genes are implicated in the etiology of male infertility, making it a very complex genetic condition. In cases of male infertility, genetic testing using next-generation sequencing (NGS) technology may be useful for diagnosis. Thus, the purpose of this investigation was to apply the diagnostic offer for genetic variant identification using an NGS panel.